Relationship of Tumor-Associated Neutrophil Expression and Neutrophil-to-Lymphocyte Ratio with Clinical Response to Neoadjuvant Chemotherapy in Locally Advanced Breast Cancer - Rahman, Abd.; ., Indra; Ferianto, Djonny; Nelwan, Berti Julian; Ardiansyah, Bau Dilam; Alvina, Yusfitaria; Faruk, Muhammad (Asian Pacific Journal of Cancer Biology, 2025)
Introduction: Breast cancer (BC) is a serious health concern. Neoadjuvant chemotherapy (NAC) is a crucial therapy for managing BC, but further research is needed to identify biomarkers that can help to predict the efficacy of this therapy. The presence and functional activity of tumor-associated neutrophils (TANs) are capable of serving as predictive biomarkers for therapeutic outcomes. Elevated neutrophil-to-lymphocyte ratio (NLR) is linked to high tumor stage and low histological grade, indicating a more aggressive disease profile. This study analyzed the relationship between TAN expression and NLR with clinical response to NAC in locally advanced BC (LABC). Methods: This was a cohort study of 41 patients with BC. TAN expression was examined using immunohistochemistry, NLR was obtained from routine blood tests, and chemotherapy response was assessed using the RECIST method. The relationship between TAN expression and NLR with chemotherapy response in LABC was tested using chi-square tests. Results: High and low TAN expression was observed in 80.5% and 19.5% of patients, respectively. For NLR before chemotherapy, 48.8% and 51.2% of patients exhibited a high and low NLR, respectively; after chemotherapy, 51.2% and 48.8% of patients exhibited a high and low NLR, respectively. Moreover, 90.2% patients responded to NAC. A significant relationship was observed between TAN expression and chemotherapy response in BC, with a moderately strong negative correlation. Conclusion: TAN expression is an important potential predictor of chemotherapy response in LABC. By identifying biomarkers like TAN, clinicians may be better able to customize treatment plans and enhance outcomes for patients with LABC.